Lyapunov Exponent-Based Study of Chaotic Mechanical Behavior of Concrete under Compression - Yuhu Quan; Xu Yang (Advances in Civil Engineering)
Chaos theory is advantageous in achieving a deeper understanding of the nonlinearity and randomness of concrete behavior. In this study, the experimental data of concrete under compression were examined and discussed using Lyapunov exponent. According to the value of the Lyapunov exponent, which was larger than 0, it could be quantitatively demonstrated that measured and fitted data exhibited chaotic features. Besides, the mechanical behavior of concrete could be predicted by deducing its evolution equation. Furthermore, the evolution and trends of the Lyapunov exponent indicated that the series with human intervention showed a stronger chaotic property, which led to the result that this kind of series might be more difficult to predict.